Gender in the Bandung City Electronic Stunting Data Collection (e-Penting) Program: Policy, Monitoring And Evaluation - Willya Achmad; Yulianah Yulianah (Journal of Governance, 2023)
This research aims to analyze the role of gender in the Electronic Stunting Data Collection Program (e-important) in Bandung City, with a focus on policy, monitoring and evaluation in preventing stunting. This research uses a qualitative approach with descriptive methods. The research results show that the e-Penting program in Bandung City has had a positive impact in recording stunting data with a strong gender mainstreaming approach. The data collected involved the active participation of women at various levels, from posyandu to sub-districts, producing more in-depth information about the impact of the program on women and men. This program successfully integrates gendered data analysis into the monitoring process, providing more comprehensive insight into gender inequality in stunting rates and access to health services. The evaluation showed that women's participation as direct users and stakeholders supported the success of the program, with women's opinions and experiences significantly integrated in the analysis of the program's successes and shortcomings. In this way, e-Penting is not only an effective tool for recording stunting data, but also a pioneer in realizing gender equality and women's empowerment through information technology innovation.